Environmental Health Risks and Housing Values: Evidence from 1,600 Toxic Plant Openings and Closings - Currie, Janet (Am Econ Rev, 2015)
Regulatory oversight of toxic emissions from industrial plants and understanding about these emissions’ impacts are in their infancy. Applying a research design based on the openings and closings of 1,600 industrial plants to rich data on housing markets and infant health, we find that: toxic air emissions affect air quality only within 1 mile of the plant; plant openings lead to 11 percent declines in housing values within 0.5 mile or a loss of about $4.25 million for these households; and a plant’s operation is associated with a roughly 3 percent increase in the probability of low birthweight within 1 mile.